2021
DOI: 10.1186/s13024-021-00458-z
|View full text |Cite
|
Sign up to set email alerts
|

Key role of the CCR2-CCL2 axis in disease modification in a mouse model of tauopathy

Abstract: Background For decades, dementia has been characterized by accumulation of waste in the brain and low-grade inflammation. Over the years, emerging studies highlighted the involvement of the immune system in neurodegenerative disease emergence and severity. Numerous studies in animal models of amyloidosis demonstrated the beneficial role of monocyte-derived macrophages in mitigating the disease, though less is known regarding tauopathy. Boosting the immune system in animal models of both amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 89 publications
(113 reference statements)
1
20
0
Order By: Relevance
“…In our previous work in 5xFAD mice, we have shown that brain disease progression is accompanied by increased Tregs in the periphery that interfere with recruitment of disease-resolving leukocytes into the brain by curtailing IFNg signaling at the choroid plexus 18,72 . In different mouse models (including 5xFAD), treatment that transiently reduced systemic Tregs or blocked the PD-1/PD-L1 inhibitory immune checkpoint pathway resulted in modification of disease course [18][19][20] and increased Tregs levels in the brain 18,71 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work in 5xFAD mice, we have shown that brain disease progression is accompanied by increased Tregs in the periphery that interfere with recruitment of disease-resolving leukocytes into the brain by curtailing IFNg signaling at the choroid plexus 18,72 . In different mouse models (including 5xFAD), treatment that transiently reduced systemic Tregs or blocked the PD-1/PD-L1 inhibitory immune checkpoint pathway resulted in modification of disease course [18][19][20] and increased Tregs levels in the brain 18,71 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of Tregs in neurodegeneration is controversial, as both protective [53][54][55][56][57][58] and harmful functions 18,57,[59][60][61] have been described, depending on location and timing 18,54,[62][63][64][65][66] . While Tregs within the brain can display anti-inflammatory activity 18,[67][68][69][70][71] , their elevation in the periphery might be harmful, as it blocks the ability of the brain to harness bone marrow-derived cells needed to clean the brain and resolve local inflammation 18 . In our previous work in 5xFAD mice, we have shown that brain disease progression is accompanied by increased Tregs in the periphery that interfere with recruitment of disease-resolving leukocytes into the brain by curtailing IFNg signaling at the choroid plexus 18,72 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking the programmed cell death Ligand 1 (PD-L1) pathway for 12 days in a DM-hTAU transgenic mice model (a mouse model of tauopathy), favored an increased accumulation of Foxp3 + T regs in the brain via the CCR 2/CCL 2 axis. Simultaneously, an improvement of the cognitive behavior, disease pathology (mainly phosphorylated tauopathy deposition in the hippocampus), neuronal survival and hippocampal inflammation, was also observed ( 89 ). Nevertheless, the increased accumulation of Foxp3 + T regs in the brain can also have detrimental effects.…”
Section: T Regs -Related Therapeutic Potential In Saementioning
confidence: 98%
“…For decades, dementia has been characterized by a buildup of waste in the brain and mild inflammation, and was shown to be influenced by the immune system ( 89 ). In a rat model of sepsis, exposure to LPS for 7 days leads to deposition of amyloid-β plaques and phosphorylated tauopathy in the hippocampus ( 23 , 109 ).…”
Section: T Regs -Related Therapeutic Potential In Saementioning
confidence: 99%